Socialization of The Importance of Knowing The Benefits of Investments and Financial Securities in Budisatriya Medan Vocational School - Amin Hou; Ester Hervina Sihombing; Sabaruddin Chaniago; Ahmad Rivai; Nasib; Martin; Ratih Amelia; Manda Dwipayani Bhastary; Widy Hastuty HS; Ahmad Fadli (Fakultas Olahraga dan Kesehatan, Universitas PGRI Banyuwangi, 2024)
There are various types of investment to choose from. Starting from real investments in physical form such as land, houses and gold as well as non-real investments in the financial sector. An example of non-real investment is investment in the financial sector such as in the capital market. Many students still don't understand the benefits of investing For this reason, education in the form of training given to students about the benefits of financial investment and the capital market will certainly be a door to change in character for students to be braver in making various investment choices in the future. The solution offered for community service carried out at SMK S Budisatrya Medan is in the form of presenting material about the benefits of investment and various ways of making financial investments in the current money market or capital market.